Kingdom of the crabs - Attenborough, David, 1926- (Sydney : BBC Enterprises Ltd., 1988)
The inhabitants of Christmas Island wake up each year just before Christmas to find legions of red crabs marching through their gardens. They scuttle to the coast to spawn, assembling for the huge communal breeding session
Keywords: Crabs -- Spawning -- Kiritimati (Kiribati).